MODEL MANAJEMEN KOPERASI SEKOLAH BERBASIS KEPEMIMPINAN VISIONER DALAM MENINGKATKAN KEMANDIRIAN SISWA - Kurnia Rizki Febriana; ⁠Nur Rokhmah Dwi Mulyasari; Rizka Nur Azizah; Shishi Mushokhiyah; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine and formulate a school cooperative management model based on visionary leadership in enhancing students' independence. School cooperatives do not only function as business units but also serve as strategic learning platforms in shaping students' independence, responsibility, and entrepreneurial spirit. Visionary leadership plays a crucial role in directing cooperative management to be more innovative, sustainable, and future-oriented. This research employs a qualitative approach using a library research method, drawing from various literature on cooperative management, educational leadership, and student character development. The findings indicate that a visionary leadership-based management model emphasizes strategic planning, participatory management, strengthening independence values, and innovative cooperative programs involving students actively. The implementation of this model has been shown to improve students' managerial skills, independence attitudes, and economic awareness. Therefore, school cooperatives can serve as effective instruments in supporting educational goals oriented toward character building and student independence. Keywords: school cooperative management, visionary leadership, student independence, character education